KONSEP SENSUALITAS DALAM ANTROPLOGI FILOSOFI FEUERBACH - Fidelis Den (STIPAS St. Sirilus Ruteng, 2023)
Human being becomes the object of reflection which is always exciting. Its definition always sparks further and in-depth discussion. The ancient philosophers saw man as a thinking animal. That is, humans are biologically the same as animals or plants that require certain natural conditions to be able to live and continue genetic development. Although he is an animal, he is an animal that can realize itself, that at a certain level, he is not much different from animals or plants. That is, he can think rationally when faced with rational things, if he is forced to think and answer questions that require reasonable answers. Modern philosophers continue to reflect on human beings by paying special attention to their rational aspects. Excessive deification of the ability of reason actually gives rise to reductional tendencies. That is, humans are only called, seen or valued as humans if they can apply rational abilities to various situations. If the brain function is disrupted, which reduces or completely eliminates the ability to think, then the quality of humanity decreases or even becomes the same as other creatures that cannot think. A further consequence of the deification of reason is the degradation of body values. The role of the body is no longer central and its presence is nothing more than a means. Feuerbach appears as a defender of the role of the human body. The body is not just a means of complementing humanity but on the contrary, humans do not only have bodies but bodies are humans themselves. The body is the totality of man. Without a body there is no identity. Being in the body means being in the middle of the world. Humans for Feuerbach are sensual creatures with various meanings. [Manusia menjadi objek refleksi yang selalu mengasyikkan. Definisi tentangnya selalu memicu diskusi lebih jauh dan mendalam. Para filsuf kuno melihat manusia sebagai binatang yang berpikir. Artinya, manusia secara biologis sama dengan hewan atau tumbuhan yang membutuhkan kondisi alam tertentu untuk dapat hidup dan melanjutkan perkembangan genetiknya. Walaupun ia adalah binatang, ia adalah binatang yang dapat menyadari dirinya sendiri, bahwa pada tingkat tertentu, ia tidak jauh berbeda dengan binatang atau tumbuhan. Artinya, ia dapat berpikir secara rasional ketika dihadapkan pada hal-hal yang rasional, jika ia dipaksa untuk berpikir dan menjawab pertanyaan yang membutuhkan jawaban yang masuk akal. Filsuf modern terus merenungkan manusia dengan memberikan perhatian khusus pada aspek rasional mereka. Pendewaan yang berlebihan terhadap kemampuan nalar justru menimbulkan kecenderungan reduksional. Artinya, manusia hanya disebut, dipandang atau dinilai sebagai manusia jika dapat menerapkan kemampuan rasionalnya pada berbagai situasi. Jika fungsi otak terganggu, yang mengurangi atau menghilangkan sama sekali kemampuan berpikir, maka kualitas manusia menurun atau bahkan menjadi sama dengan makhluk lain yang tidak dapat berpikir. Konsekuensi lebih lanjut dari pendewaan akal adalah degradasi nilai-nilai tubuh. Peran tubuh tidak lagi sentral dan kehadirannya tak lebih dari sarana. Feuerbach tampil sebagai pembela peran tubuh manusia. Tubuh bukan hanya sekadar sarana pelengkap manusia, melainkan manusia itu sendiri. Tubuh adalah totalitas manusia. Tanpa tubuh tidak ada identitas. Berada di dalam tubuh berarti berada di tengah dunia. Manusia bagi Feuerbach adalah makhluk sensual dengan berbagai makna.]